Fiber Materials Used in Prosthetic Dentistry - Cetintas, Senay; Karacaer, Ozgul; Tokar, Emre (The Journal of Dentists, 2017)
The aim of this systematic review is to examine the past daily use of fiber, the articles that evaluate the mechanical properties of fibers and the current approaches of fibers especially those used in prosthetic applications. Fiber materials have high quality properties that strengthened the material, increase the elasticity modulus and fracture strength of the material added into. This systematic review investigated the articles that pointed out all the properties of fibers used in prosthodontics.